Influence of Family, Peer Factors and Comprehensive Sexuality Education on Teenage Pregnancy in the Northeast of Thailand: A Case Control Study (Indian Journal of Public Health Research & Development, 2020)
Background: More than one third of teenage pregnancies was found in the Northeast of Thailand. Theobjective of this research was to examine the influence of personal, family, peer factors, sexuality attitude,and the comprehensive sexuality education (CSE) on teenage pregnancies in the Northeast of Thailand.Methodology: This case control study was conducted with the 1:3 proportion of case and control. Thecase were 60 teenage aged 15-19 years old, lived in the Northeast of Thailand, and delivered a baby lessthan 1 years. The control was 180 teenagers aged between 15 and 19 years old in the same region but neverpregnant. Multiple logistic regression analysis was used to identify factors associated with teenage pregnancypresenting adjusted odds ratio and 95% confident Interval for the magnitude of association. P-value of
Keywords: Environment, Family, Northeast of Thailand, Peer, Teenage Pregnancy